2017
DOI: 10.1007/s12288-017-0821-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of FLT3 and NPM1 Mutations in Acute Myeloid Leukaemia Patients of Assam, India

Abstract: Acute Myeloid Leukaemia (AML) is one of the common forms of haematological malignancy in adults. We analysed the prevalence and clinical significance of FMS-like tyrosine kinase 3 (FLT3) and Nucleophosmin 1 (NPM1) mutations in AML patients of North East India. Co-prevalence and clinical significance of three recurrent chromosomal translocations namely t(15; 17), t(8; 21), t(16; 16) and expression of epidermal growth factor receptor (EGFR), flow markers were also documented and co-related with disease progress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…Although cytogenetics is the most valuable prognostic marker in AML, however in patients with normal karyotype, molecular tasting like FLT3-ITD mutation has an important role as a prognostic risk stratification for those patients, and therefore optimizing better therapeutic approaches. 21 The current study demonstrated that FLT3-ITD mutation represented 17.6% of the assessed Egyptian AML patients. This percentage was comparable to other studies which reported the prevalence of FLT3-ITD mutation which were 17.4%, 15.9%, and14.6% in Latin American, Chinese, and Indian patients, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Although cytogenetics is the most valuable prognostic marker in AML, however in patients with normal karyotype, molecular tasting like FLT3-ITD mutation has an important role as a prognostic risk stratification for those patients, and therefore optimizing better therapeutic approaches. 21 The current study demonstrated that FLT3-ITD mutation represented 17.6% of the assessed Egyptian AML patients. This percentage was comparable to other studies which reported the prevalence of FLT3-ITD mutation which were 17.4%, 15.9%, and14.6% in Latin American, Chinese, and Indian patients, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Also, Wang et al 32 concluded a significant increase in the BM blast cell count and TLC in AML patients with FLT3-ITD mutation. On the other hand, Bhattacharyya et al 21 detected a significant increase in the TLC in AML patients with FLT3-ITD mutation, however no significant association with PB or BM blast cell count.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations